Efektivitas Model Pembelajaran Problem Based Learning (PBL) dengan Pendekatan Teaching At The Right Level (TARL) Terhadap Kemandirian Belajar Pai dan Budi pekerti peserta didik - oktavia intan isyadi; Ruswanto Ruswanto; Ais Istiana (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study aims to test the effectiveness of the Problem Based Learning (PBL) learning model combined with the Teaching at the Right Level (TaRL) approach on students' learning independence in Islamic Religious Education (PAI) and Character Building subjects at SMA Negeri 1 Tanjung Bintang. This study used a quasi-experimental design with two sample groups, namely the experimental class that implemented PBL-TaRL integration and the control class that used conventional learning. Data analysis was carried out through prerequisite tests (normality and homogeneity) and t-tests to identify differences in the average learning independence between the two groups. The results showed that the implementation of PBL integrated with the TaRL approach significantly increased students' learning independence compared to conventional learning. This increase was especially seen in the initiative and creativity indicators in the learning process. Pedagogically, the PBL-TaRL integration created a more participatory, collaborative, and adaptive learning environment to differences in students' ability levels, thus encouraging the development of self-regulation and learning responsibility. The novelty of this study lies in the integrative design between PBL and TaRL in the context of PAI learning at the high school level, which is still relatively limited in empirical studies. Theoretically, these findings expand the development of problem-based learning models combined with a differentiation approach, in line with the constructivist perspective and the concept of the zone of proximal development, which emphasizes the importance of learning support tailored to the student's ability level. Practically, the results of this study provide implications for Islamic Religious Education (PAI) teachers in developing more adaptive, inclusive, and contextual learning strategies, and serve as a basis for schools in designing learning policies oriented towards strengthening independent learning. Thus, this research contributes to the development of Islamic education theory and practice that is responsive to the needs of students in the 21st-century learning era.